Opinion paper: COVID-19 and the livestock sector - Ani, A. O.; Baes, C.; Chemineau, P.; Gauly, M.; Jiménez-Flores, R.; Kashiwazaki, N.; Kegley, E. B.; Kembe, M. A; Loh, T. C.; Maiwashe, A.; Medina-Villacìs, M.; Rosati, A. (Elsevier, 2021)
Pandemics are a recurring theme in human history, with evidence from the beginning of civilization up to the current Corona virus disease 2019 (COVID-19) pandemic. The genotype of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus that has paralyzed the entire world since early 2020 is most closely related to a coronavirus from bats, eventually passed via Pangolins, although is not identical (Zhu et al., 2020). One of the most accredited hypotheses is that the virus first infected a human at or near a wet market in Wuhan, in the Hubei region of China; this city was the epicenter of the outbreak. In spite of some dis-information which circulates in the social media, it is clear that the virus originates in the over-exploitation of a wildlife at risk of transmission of diseases to humans and, moreover, in danger of extinction. In spite of the very numerous alerts which have been given in the past about the risk of a major outbreak coming from bats which host a high number of SARS viruses, the uncontrolled use of wildlife as a source of meat, bones, scales, blood, horns, hair and many other tissues has never ceased. These products, coming from poaching of endangered and not farmed species, feed both un-official and official markets of food or/and pharmacopeia. We should clearly affirm here that these processes should stop in a near future as they are not only destroying biodiversity but also producing pandemics which have major socio-economical consequences.